Method evaluation of GIS-based prediction tools for biodiversity - Birgersson, Malin (2007)
Swedish cities are from a European point of view considered small, sparsely populated and green. Stockholm city has a great deal of its nature and older cultural landscape remaining, which is unusual in large metropolitan areas.